2013
DOI: 10.1167/iovs.13-12274
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Cytokines in Glaucomatous Aqueous and Encysted Molteno Implant Blebs and Their Relationship to Pressure

Abstract: The study confirms the well documented presence of TGF-β2 in glaucomatous aqueous. The presence of significant levels of CCL2 in glaucomatous aqueous is a new finding. The finding of higher levels of all the cytokines in the aqueous from the encysted blebs, in which the IOP was the highest, suggests that their levels increase with an increase in IOP, as well as the possibility that encysted blebs form cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 16 publications
2
69
1
Order By: Relevance
“…The significant correlations between these cytokines and the IOP levels suggested a strong link between inflammatory cytokine networks and IOP elevation, although the exact mechanism of this interaction is unclear. Recently, Freedman and Iserovich 26 have proposed that the increase in cytokine levels that parallels the increase in IOP is highly suggestive of IOP as a potential stimulus for cytokine production. In the present study, the highest levels of cytokines were found in the aqueous humor taken from eyes with the highest IOP (i.e., the current APAC group).…”
Section: Inflammation-related Cytokines In Aqueous Humor In Apacmentioning
confidence: 99%
“…The significant correlations between these cytokines and the IOP levels suggested a strong link between inflammatory cytokine networks and IOP elevation, although the exact mechanism of this interaction is unclear. Recently, Freedman and Iserovich 26 have proposed that the increase in cytokine levels that parallels the increase in IOP is highly suggestive of IOP as a potential stimulus for cytokine production. In the present study, the highest levels of cytokines were found in the aqueous humor taken from eyes with the highest IOP (i.e., the current APAC group).…”
Section: Inflammation-related Cytokines In Aqueous Humor In Apacmentioning
confidence: 99%
“…62 These inflammatory mediators and cytokines are upregulated not only at the surgical site, but within the glaucomatous aqueous: increased levels of transforming growth factor-b 2 have been described in people 63 and dogs. 64 Glaucoma and vascular endothelium growth factor was upregulated in the AH of canine 65 and human glaucomatous patients and in the rabbit model of filtration surgery.…”
Section: Filtering and End-stage Glaucoma Proceduresmentioning
confidence: 99%
“…60 Rapid inflow of growth-factor-laden AH through the filtering device may enhance the recruitment and proliferation of episcleral fibroblasts and precipitate bleb fibrosis. 63 Because of this inflammatory priming at the surgical subconjunctival site, the placement of a second implant in the same area in case of bleb failure is not recommended. 63,66 A whole body of literature has reported the occurrence of significant ocular surface changes associated with chronic use of topical antiglaucoma medications.…”
Section: Filtering and End-stage Glaucoma Proceduresmentioning
confidence: 99%
“…The causes of IOP elevation are variable, and can include degeneration of the trabecular meshwork, formation of peripheral anterior synechiae, and other causes. Dysfunction of the filtering bleb, however, is suspected to contribute to uncontrolled IOP in most cases, because inflammatory reactions at the bleb site cause vasodilation, production of inflammatory cytokines, and other problems, resulting in fibrosis at and around the filtering bleb [8,9]. It is well known that bleb morphology is highly correlated with IOP control [10,11], and that bleb size and intra-bleb reflectivity have predictive value for IOP after filtering surgery.…”
Section: Introductionmentioning
confidence: 99%